Усреднение задач Неймана для нелинейных эллиптических уравнений в областях каркасного типа с тонкими каналами - Ковалевский, А.А. (Український математичний журнал, 1993)
TheG-convergence of operators of the Neumann problem is established in regions with framework-type periodic structure with thin channels. A representation of the coefficients of aG-limiting operator is obtained.